Kajian Dampak Pariwisata Berbasis Masyarakat sebagai Pendukung Sustainable Development terhadap Peningkatan Wisatawan di Daerah Istimewa Yogyakarta - Nasution, Olivia Barcelona; Primandaru, Noormalita (Lasigo Akademia Indonesia, 2023)
The issue of sustainability has become the focus of attention of practitioners, governments and researchers in all contexts, including the tourism sector, so it is important to examine the impact of one form of tourism sustainability, namely community based tourism (CBT) on tourists' desire to revisit tourism destinations. This study aims to examine perceptions of CBT performance on satisfaction and its impact on revisit intention and word of mouth (WOM) intention. This research uses primary data by distributing questionnaires online. The characteristics of the respondents in this research are people who have visited tourist destinations in DI Yogyakarta. A total of 168 respondents were collected. Data were analyzed using structural equation models using SmartPLS 3.2.9 software. The tests carried out consisted of testing the measurement model and testing the inner model. The research results show that the performance of community based tourism (CBT) has a significant effect on tourist satisfaction, tourist satisfaction has a significant effect on intention to revisit, and tourist satisfaction has a significant effect on word of mouth. The results of this research suggest that tourism developers and the government can collaborate and regularly measure CBT performance so that they continue to provide pleasant services and experiences to tourists so that tourists visit again and even voluntarily invite other people to visit tourist destinations.